Above the forest : a study of Andamanese ethnoanemology, cosmology, and the power ritual - Pandya, Vishvajit (Delhi ; New York : Oxford University Press, 1993)
Study on Onge, Indic people.
Maps on lining papers.
Keywords: Onge (Indic people) -- Social life and customs; Onge (Indic people) -- Religion; Andaman and Nicobar Islands (India) -- Social life and customs; Andaman and Nicobar Islands (India) -- Religion